Bioremediation of hexavalent chromium by bacterial strains isolated from chromium contaminated site (International Journal of Food and Nutritional Sciences, 2022)
Chromium contamination due to increased industrial activities poses a serious threat to people’s health and the surrounding environment. The bioreduction of highly toxic Cr(VI) to less toxic Cr(III) is a promising alternative to chemical chromium remediation methods. In this study, ten bacterial strains were isolated from the soil samples of leather tanning industries and subjected to analysis of their Cr(VI) resistance and reduction. The isolates C5, C8, C14, C16, and C20 were found to be resistant to 1000 mg/l Cr(VI). Of the five isolates, C5, C8, and C20 reduced the Cr (VI) of (1000 mg/l) by 80%, 89%, and 84%, respectively, when analysed using the diphenylcarbazide assay. The potentiality of C8 (highest Cr VI reduced strain) to remediate toxicity of Cr(VI) on plants was assessed on Vigna radiata (Green gram), which shown significant improvement in the seed’s germination and plant growth of Vigna radiata in the presence of Cr(VI) treated with C8 than untreated, proving its capability to remediate Cr(VI) contamination by reducing the phytotoxicity of Cr(VI). By gram staining, the bacterial strain (C8) was identified as a gram-negative cocci, and biochemical analysis revealed that it was positive for the indole test. This study suggests that the bacteria found in Cr-contaminated sites could resist and reduce Cr(VI) at a very high level, making it a promising and feasible approach for the remediation of Cr contamination.